Choroidal Thickness and Peripheral Myopic Defocus during Orthokeratology. Issue 5 (May 2015) - Gardner, Dustin J.; Walline, Jeffrey J.; Mutti, Donald O.
ABSTRACT: Purpose: To investigate whether significant thickening occurs in the human choroid in response to chronic peripheral myopic defocus during overnight orthokeratology. Methods: Subjects were nine children 11 to 15 years old (mean [±SD] age, 13.61 [±1.25] years). Measurements were taken at baseline and after 1, 3, 6, and 9 months of successful orthokeratology. Choroidal thickness in central, superior, temporal, and nasal gazes were measured using the Zeiss Cirrus HD-OCT. The Lenstar LS 900 biometer provided a secondary measure of subfoveal choroidal thickness. Peripheral ocular length was measured in the same four fields of gaze with the Zeiss IOLMaster. Corneal and optical changes from orthokeratology were monitored throughout the study by corneal topography (Humphrey ATLAS), aberrometry (Complete Ophthalmic Analysis System), and central and peripheral autorefraction (Grand Seiko) after tropicamide 1% cycloplegia. Results: All subjects had acceptable acuity and physiologic response to overnight wear. After 1 month, central refractive error (mean ± SD) became significantly less myopic (−2.25 ± 0.95 diopters [D] vs. −0.24 ± 1.03 D), keratometric values flattened by 1.6 D, the shape factor ( Q ) became more oblate (−0.28 ± 0.05 vs. +0.34 ± 0.41), and spherical aberration became more positive (+0.14 ± 0.08 μm vs. +0.46 ± 0.15 μm; all p = 0.008). Peripheral refractive error remained −1.0 to –3.5 D myopic in all fields of gaze throughout the study. There were no consistent, significant changes in choroidal thickness or ocular length at any retinal location during the study (all p > 0.051). Lenstar measurement of choroidal thickness was unsuccessful because of the absence of choroidal peaks associated with thicker choroids ( r s = −0.66, p < 0.0001). Conclusions: The choroid did not show long-term thickening during orthokeratology despite the presence of substantial amounts of peripheral myopic defocus. Apparent inhibition of ocular growth was not attributed to an optical artifact of choroidal thickening, although smaller amounts of thickening or greater biological activity independent of thickening cannot be ruled out.